Marine Mining And Minerals Exploration: The New Role For Academe - J. Robert Moore (International Marine Minerals Society, 1986)
Introductory remarks will be made by the speaker, chiefly on recent and current developments in the industrial, agency and academic sectors that relate to the status of marine mining and mineral exploration programs and to recommendations for strengthening and continuing these programs. Subsequent to these brief comments, a selected panel with representation from industry, academe and government will address the following related topics: 1) development and objectives of new centers for marine mining technology, 2) cooperative R. and D. programs between academe and the user groups, 3) arrangements for specialized training and student instruction that will provide for educational components, and 4) funding and other support for implementing new centers and new programs. The panel discussion will be open to all UMI participants and whose contributions will be both solicited and encouraged.